Integrasi Nilai Lempu’ dalam Aplikasi Expressive Writing Untuk Meningkatkan Self-disclosure Siswa kepada Guru BK sebagai Upaya Menuju Indonesia Emas 2045: Integrating Lempu’ Values into Expressive Writing Activities to Enhance Students’ Self-Disclosure to Guidance Counselors as a Step Toward Indonesia Emas 2045 - Putri Anggun Sudirman; Andi Nur Afiyah Azzahrah; Raden Dimas; Aswar (Litera Academica Publishing, 2026)
Low levels of students’ self-disclosure toward school counselors, caused by a lack of trust, hinder the effectiveness of the counseling process. This study aims to formulate an innovative solution by integrating the value of lempu’ into an expressive writing application to enhance students’ self-disclosure. This research employs a qualitative approach using a literature review design, conducted through the following stages: (1) topic selection; (2) source collection; (3) literature analysis; (4) synthesis; and (5) conclusion drawing. A conceptual analysis was then conducted, emphasizing four main components: counseling services, local wisdom, digital innovation, and the Vision of Indonesia Emas 2045. The findings indicate that an expressive writing application based on the value of lempu’, functioning as a cathartic medium, can strengthen students’ self-disclosure toward school counselors. This integrated model not only has the potential to effectively enhance students’ self-disclosure but also supports the development of the younger generation’s character toward Indonesia Emas 2045.